Social stratification and cultural consumption: cinema going and choice of movie genres in Athens - Καυταντζόγλου Ρωξάνη; Εμμανουήλ Δημήτρης (The Greek Review of Social Research, 2016)
The article focuses on the relationship between social stratification and consumption of culture, namely cinema-going and the choice of film genres. The research findings are interpreted in light of the ongoing debate between P. Bourdieu’s theory of Distinction, the post-modernists’ individualisation argument, R. Peterson’s ‘omnivore’ model and B. Lahire’s theory of cultural dissonance. A central tenet of the approach is the neo-weberian distinction between status and socio-economic class. While our findings indicate the partial prevalence of the distinction mechanism advanced by Bourdieu, it should also be noted that there is no support of a systematic ‘homology’ between class and culture. Tendencies toward omnivorousness and cultural dissonance are present, albeit at very low rates.